PENGARUH PROSES M EMBRAN U LTRAFILTRASI DAN ULTRAVIOLET TERHADAP KOMPOSISI GIZI, SIFAT FISIKOKIMIA DAN ORGANOLEPTIK MINUMAN AIR KELAPA / The Effects of Ultrafiltration and Ultraviolet Process on Nutritional Composition, Physicochemical and Organoleptic - SARI INTAN KAILAKU; BUDI SETIAWAN; AHMAD SULAEMAN (Jurnal Penelitian Tanaman Industri, 2016)
The obstacle in developing coconut water-based product is its easily altered properties. Ultrafiltration and ultraviolet processing are potential to obtain a longer shelf life for coconut water drink without altering its nutritional values and unique organoleptic properties, unlike other processing techniques e.g. pasteurization and ultra high temperature. Shelf-life estimation experiment showed that ultrafiltration-and- ultraviolet-processed coconut water without any addition of food additives can be stored for 51 days in 00C. The objective of this research was to evaluate the effects of ultrafiltration and ultraviolet treatments on the nutritional, physicochemical and organoleptic properties of coconut water drink. The experiments were carried out at Food Analysis Laboratory, Indonesian Center of Agricultural Postharvest Research and Development, on January-April 2015. Coconut water was flown through the ultrafiltration membrane unit and ultraviolet light unit, samples were collected in three repetitions. Nutritional composition and physicochemical properties of fresh coconut water (FCW) and coconut water drink obtained from ultrafiltration and ultraviolet process (CUU) were evaluated and compared. Organoleptic analysis was done by 20 panelists, observations included quality hedonic (aroma, sweetness, saltiness, sourness and turbidity), and acceptance (preferance and ranking test), comparing FCW and CUU with commercial coconut water drink (CWD). CUU showed indistinguishable nutritional composition and physicochemical characteristics from FCW (p>0,05), except on total sugar (p=0,049), clarity (p=0,001), L* (lightness) (p=0,000) and b* (yellowish) (p=0,002). Panelists gave CUU a statistically equal rank to FCW, and better than CWD. The organoleptic characteristics of CUU were concluded as relatively same in saltiness and aroma as FCW, and less intense in sweetness and turbidity compared to CWD. After 10 days storage, panelists level of liking was higher for CUU compared to CWD in color (p=0,004) and general appearance (p=0,016).Keywords: coconut water, nutritional composition, organoleptic properties ultrafiltration, ultraviolet